Voice and Leadership for Women on Fisheries Aspects and Governance Issues - Kilanga, Lucyphine; Kakwasha, Keagan; Kitogo, Lawrence; Simbila, Deogratius; Muzungaire, Lizzy; Chileya, Agness; Lukanga, Editrudith; Mudege, Netsayi (WorldFish, 2024)
This report presents the outcome of the activities conducted in Muleba District in 2024 to strengthen the voice and leadership among women in eight communities/islands. The project made training, coaching, and mentorship visits to 200 women fish processors and traders. The capacitation was done in collaboration with representatives of Beach Management Units (BMUs), fisheries officers, and EMEDO. All targeted women were members of TAWFA, which is a chapter of the continental African Women Fish Processors and Traders Network (AWFISHNET).